Evaluasi dan Rekomendasi Pengelolaan Limbah Bahan Berbahaya dan Beracun Pada Industri Pembuatan Suku Cadang di PT X, Kota Surabaya - Moch Shafansyah Yumna Argia; Muhammad Faisal Fadhil (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study aims to evaluate the management of hazardous and toxic waste (B3) at PT. X, a spare parts manufacturing industry in Surabaya. Hazardous waste management is a major challenge in this industry due to its hazardous, corrosive, flammable and environmentally harmful properties if improperly handled. Data was collected through field observations, interviews with relevant stakeholders, and analysis of regulations and company reports. The results show that PT. X's level of compliance in hazardous waste management is 61.1%, which is considered fair but not ideal. Key deficiencies were identified in the areas of packaging, labelling and storage. The waste packaging does not fully match the waste characteristics, while the labelling is fragile and lacks complete information. In addition, the storage area is located within the production area, making it unsafe and difficult to access. To improve the management of hazardous waste, the study recommends the use of appropriate packaging materials, durable labels with comprehensive information, and the design of storage facilities that meet regulatory standards. Implementing these recommendations is expected to improve the effectiveness of hazardous waste management, reduce pollution risks and protect both the environment and human health.